Self-Regulated Learning Of University Students In Digital Learning: Scoping Review - Aji Bagus Priyambodo; Fitri Andriani; Pramesti Pradna Paramita (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Entering the education revolution 5.0, the digitalization of learning in higher education is growing increasingly massive, but on the other hand there are still many students who have problems in Self-Regulated Learning (SLR) which has an impact on achieving learning outcomes that are not optimal. This study aims to describe student's application of SRL in digital learning along with things that influence student’s SRL in their learning practices. This study is a scoping review sourced from the ScienceDirect and EBSCOhost databases. Population (P) in this literature study are college students, Concept (C) that will be studied is self-regulated learning (SRL) and Context (C) in this study is digital learning. The publication year limit is between 2019-2024, resulting in a total of 71 articles. Duplication testing was carried out using Zotero and Rayyan to obtain 12 articles that met the inclusion criteria, then continued with the charting process using the Elicit application which was then validated using manual analysis from the author. From the results of the study it can be concluded that student's implementation of SRL strategies is reflected in their independence in using various digital learning tools. The form of SRL strategy in student digital learning includes personal functions, behavioral functions and environmental functions. Apart from that, there is the role of individual meaning of the learning environment which also influences the interaction of these three functions in forming students' SRL. Things that influence SRL in student digital learning include internal factors and external factors. In this study, the dynamics of SRL function and its determinants are discussed using a multi-perspective approach.